2020
DOI: 10.1177/0300985820960131
|View full text |Cite
|
Sign up to set email alerts
|

FoxP3, CTLA-4, and IDO in Canine Melanocytic Tumors

Abstract: Despite promising immunotherapy strategies in human melanoma, there are few studies on the immune environment of canine melanocytic tumors. In humans, the activation of immunosuppressive cell subpopulations, such as regulatory T cells (Tregs) that express forkhead box protein P3 (FoxP3), the engagement of immunosuppressive surface receptors like cytotoxic T lymphocyte antigen (CTLA-4), and the secretion of molecules inhibiting lymphocyte activation, such as indoleamine-pyrrole 2,3-dioxygenase (IDO), are recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 84 publications
1
33
0
Order By: Relevance
“…The presence of few CTLA-4 positive cells within the tumor microenvironment in the context of a negativity of tumor cells seems to indicate that this pathway is not particularly involved in the immunoescape of epSCCs. Still, further studies on CTLA-4 expression in veterinary neoplastic diseases are necessary as currently available data are still few [34,39,40]. To the best of the authors' knowledge, this was the first time CTLA-4 was investigated in horses.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The presence of few CTLA-4 positive cells within the tumor microenvironment in the context of a negativity of tumor cells seems to indicate that this pathway is not particularly involved in the immunoescape of epSCCs. Still, further studies on CTLA-4 expression in veterinary neoplastic diseases are necessary as currently available data are still few [34,39,40]. To the best of the authors' knowledge, this was the first time CTLA-4 was investigated in horses.…”
Section: Discussionmentioning
confidence: 96%
“…Then, slides were washed with PBS and incubated in 3% H 2 O 2 for 10 min. After a protein blocking step, the incubation with rabbit polyclonal anti-PD-L1 and mouse monoclonal anti-CTLA-4 [34] antibodies was performed. After secondary biotinylated antibody and streptavidin incubation, immunolabeling was revealed with AEC.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The primer set is reported in Table 2. As previously described [31,32] a Real-Time PCR amplification using SsoFast EvaGreen Supermix (BioRad, Hercules, CA, USA) was performed in a CFX96 Real-Time System with 5 µL of 1:5 diluted cDNA. Each sample was tested in triplicate and fluorescence data were collected at the end of the second step of each cycle.…”
Section: Rt-qpcr For Host Gene Studymentioning
confidence: 99%
“…Therefore, naturally occurring cancer in pet dogs is an ideal animal model for studying complex immune interactions during cancer treatment (27)(28)(29). Various studies have shown that the CTLA-4 plays a similar role in canine cancer (30). However, ICIs for CTLA4 blockade are not commercially available for canine cancer patients due to the lack of species-speci c mAbs.…”
Section: Introductionmentioning
confidence: 99%
“…Nanobodies (Nbs), representing the variable fragments (VHH) of camelid heavy-chain-only antibodies (HcAbs), bind to antigens in the absence of a light chain (14). Nbs are small in size (~ 15kDa) and bind to antigens with high speci city and a nity like conventional mAbs (30,31,33). Nbs or Nb-based molecules are in different stages of development for cancer diagnosis and therapy (31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%